1996
DOI: 10.1016/s0092-8674(00)81063-6
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahymena Histone Acetyltransferase A: A Homolog to Yeast Gcn5p Linking Histone Acetylation to Gene Activation

Abstract: We report the cloning of a transcription-associated histone acetyltransferase type A(HAT A). This Tetrahymena enzyme is strikingly homologous to the yeast protein Gcn5, a putative transcriptional adaptor, and we demonstrate that recombinant Gcn5p possesses HAT activity. Both the ciliate enzyme and Gcn5p contain potential active site residues found in other acetyltransferases and a highly conserved bromodomain. The presence of this domain in nuclear A-type HATs, but not in cytoplasmic B-type HATs, suggests a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
972
1
12

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,464 publications
(1,000 citation statements)
references
References 58 publications
15
972
1
12
Order By: Relevance
“…HAT complexes from both GNAT and MYST families were shown to be recruited to activator-bound nucleosomes resulting in transcriptional activation (Brownell et al, 1996;Vignali et al, 2000;Utley et al, 2005). The recruitment of SAGA leads to acetylation of promoter-proximal H3, whereas recruitment of NuA4 results in a broader domain of H4 acetylation (>3 kbp) (Vignali et al, 2000).…”
Section: Transcriptionmentioning
confidence: 99%
“…HAT complexes from both GNAT and MYST families were shown to be recruited to activator-bound nucleosomes resulting in transcriptional activation (Brownell et al, 1996;Vignali et al, 2000;Utley et al, 2005). The recruitment of SAGA leads to acetylation of promoter-proximal H3, whereas recruitment of NuA4 results in a broader domain of H4 acetylation (>3 kbp) (Vignali et al, 2000).…”
Section: Transcriptionmentioning
confidence: 99%
“…Recent studies have shown that HAT acts as the transcriptional coactivator (Bannister and Kouzarides, 1996;Brownell et al, 1996;Mizzen et al, 1996;Ogryzko et al, 1996;Yang et al, 1996b) whereas HDAC behaves as the corepressor Hassig et al, 1997;Kadosh and Struhl, 1997;Laherty et al, 1997;Nagy et al, 1997;Yang et al, 1996a). Therefore, it seems reasonable that HDAC inhibitors exhibit various biological activities by directly a ecting the transcription of some endogenous genes.…”
Section: E Ects Of Oxam¯atin On Endogenous Gene Expressionmentioning
confidence: 99%
“…Overall, it is proposed that acetylation levels regulate gene transcription by controlling the accessibility of transcription factors to DNA (Grunstein, 1997). Indeed, HAT and HDAC activity has been identified within transcriptional coactivators and corepressors, respectively, providing strong evidence of the functional connection between histone acetylation and transcription (Brownell et al, 1996;Alland et al, 1997).…”
Section: Introductionmentioning
confidence: 99%